Análisis de la situación de pobreza en Medellín a partir de la encuesta de calidad de vida, 2004-2005 (2009)
This work analyses the results of the Standard of Living Surveys (SFSs) conducted in Medellín during 2004 and 2005 in order to establish the city's advances in human development and standard of living in the administration period of former mayor Sergio Fajardo up to 2006. This article is framed into the human development poverty theory. It disentangles both the Human Development Index and the Standard of Living Index by components. Also, it makes a criticism to the design of the SFS in Medellín. And, finally, it computes UNDP's Human Poverty Index as a complementary measure. The article concludes that it is very difficult to identify changes in poverty from one year to the other and recognizes the municipal government's effort for generating an information mechanism on this issue.